Indeks glikemik cookies growol: studi pengembangan produk makanan selingan bagi penyandang diabetes mellitus - Desty Ervira Puspaningtyas; Puspita Mardika Sari; Nanda Herdiyanti Kusuma; Debora Helsius SB (Jurnal Gizi Klinik Indonesia, 2020)
Glycemic index of growol cookies: snack development study for people with diabetes mellitusBackground: Low-glycemic foods with high fiber content have been shown to control blood glucose in diabetics. Growol, cassava fermented food, can be potentially developed as a functional food for diabetics. Growol has higher dietary fiber and lower total sugar, reducing sugar, and sucrose compared to cassava. Carbohydrates in growol combined with roasting processing techniques into cookies products may potentially change the glycemic index of the product.Objective: To examine the potency of growol cookies as a snack for diabetics in terms of the glycemic index of cookies.Methods: This observational laboratory study analyzed the glycemic index of growol cookies compared to glucose and control cookies. The study was conducted from April to October 2019. Ten subjects were involved in the glycemic index measurement. The glycemic index was analyzed through the area under the curve (AUC) ratio of glucose response of food by measuring blood glucose levels during fasting; 30; 60; 90; and 120 minutes after consuming test foods (growol cookies and control cookies).Results: AUC for glucose, control cookies, and growol cookies were 13,669.5; 11,886; and 11,941.5. The glucose glycemic index was 100, while the glycemic index of control cookies and growol cookies was 87. Both control cookies and growol cookies are high glycemic index food. There was an AUC difference between glucose and control cookies (p=0.001) and between glucose and growol cookies (p=0.001). The difference in AUC between control cookies and growol cookies (p=0.991) was not seen.Conclusions: Growol cookies have a lower glycemic index than glucose, but it still cannot be consumed as an alternative snack for diabetics.